Treatment of the Cheyne-Stokes Breathing Pattern in Patients with Congestive Heart Failure: An Update - Wallace, Jeanne; Poon, Charles (Current Respiratory Medicine Reviews, 2013)
Cheyne-Stokes breathing/central sleep apnea (CSB/CSA) commonly occurs in patients with congestive heart failure. Since our previous review, there has been further evidence supporting the clinical significance of this primarily nocturnal breathing disorder in terms of the associated physiologic and biochemical changes that may lead to further deterioration of cardiac function, as well as increased mortality. Suppression of CSB/CSA can be difficult to achieve and a consistently effective therapeutic strategy has not been identified. Although optimizing medical management of the underlying heart failure would be a logical initial intervention, lower prevalence of CSB/CSA has not been observed in groups of patients receiving modern medical therapy. Recently published guidelines have supported nocturnal oxygen, CPAP and adaptive servo-ventilation as standard recommendations for treatment. Further evidence since the last review has backed pacemaker resynchronization as an effective means of suppressing CSB/CSA. Early studies on the feasibility of phrenic nerve stimulation as a means for interrupting CSB/CSA period breathing have shown promise. Other methods including positional therapy, carbon dioxide and acetazolamide have continued to show effect in attenuating CSB/CSA in some patients. More recently, combination therapies, such as nocturnal oxygen and CPAP have been suggested as alternative treatment approaches for CSB/CSA, but have not yet been validated by published evidence. The interaction between HF and SDB are complex, and call for close collaboration between cardiologists and pulmonary specialists for optimal care of patients with these disorders.
Keywords: heart failure